1979
DOI: 10.1002/j.1552-4604.1979.tb02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Sotalol Therapy in Patients with Arrhythmias

Abstract: Sotalol is a pure beta-adrenergic receptor antagonist. The present study was divided into a first and second therapy period. A total of 38 patients with atrial or ventricular arrhythmias were included in the first therapy period. After a drug-free period of approximately two months, 14 of the 38 patients entered the second therapy period and were given oral sotalol. During the two treatment periods, oral sotalol was given in doses ranging from 40 to 480 mg/day for 0.5 to 11 months in the first period and for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…5 Subsequent studies in patients have confirmed that sotalol administered over the both the short and long term lengthens repolarization and refractoriness in the heart.7-9 Its so-called class III5 antiarrhythmic actions have also been confirmed from the direct recordings of monophasic action potentials via suction electrodes in man.7-9 However, there remains a paucity of data dealing with the effect of sotalol on cardiac arrhythmias. [10][11][12][13][14] The purpose of the the present study was to evaluate the efficacy and safety of sotalol in patients with symptomatic, sustained, life-threatening ventricular tachyarrhythmias. The study was conducted in two parts.…”
mentioning
confidence: 99%
“…5 Subsequent studies in patients have confirmed that sotalol administered over the both the short and long term lengthens repolarization and refractoriness in the heart.7-9 Its so-called class III5 antiarrhythmic actions have also been confirmed from the direct recordings of monophasic action potentials via suction electrodes in man.7-9 However, there remains a paucity of data dealing with the effect of sotalol on cardiac arrhythmias. [10][11][12][13][14] The purpose of the the present study was to evaluate the efficacy and safety of sotalol in patients with symptomatic, sustained, life-threatening ventricular tachyarrhythmias. The study was conducted in two parts.…”
mentioning
confidence: 99%
“…In 27 patients with ongoing atrial fibrillation/flutter, 1 1 / 16 patients responded to sotalol at an average intravenous dose of 0.7 mg/kg (68). Similarly, intravenous sotalol(40-100 mg) terminated atrial fibrillation/flutter in 6/ 1 1 other patients (58).…”
Section: Supraventricular Arrhythmiasmentioning
confidence: 99%
“…Neither arrhythmogenic nor adverse effects were observed. Oral sotalol was also effective in uncontrolled trials, both acutely and chronically, in patients with PVCs and various types of underlying heart disease (5,44,58). In a study that examined the relationship among P-adrenoceptor antagonism, QTc prolongation, plasma levels of sotalol, and PVC suppression in 17 patients, Wang et al (72) concluded that (a) sota-lo1 was effective in a significant number of patients who had previously failed to respond to conventional @-adrenoceptor antagonists, (b) QTc prolongation occurred at significantly higher doses than P-adrenoceptor antagonism, and (c) QTc prolongation probably contributed to the antiarrhythmic activity of sotalol.…”
Section: Complex and Repetitive Pvcsmentioning
confidence: 99%
See 1 more Smart Citation